Computationally assessing diamond as an ultrafast pulse shaper for high-power ultrawideband radar - Herrmann, Christopher S.; Croman, Joseph; Baryshev, Sergey V. (Frontiers in Carbon, 2023)
Diamond holds promise to reshape ultrafast and high-power electronics. One such solid-state device is the diode avalanche shaper (DAS), which functions as an ultrafast closing switch where closing is caused by the formation of the streamer traversing the diode much faster than 107 cm/s. One of the most prominent applications of DAS devices is in ultrawideband (UWB) radio/radar. Here, we simulate a diamond-based DAS and compare the results to a silicon-based DAS. All DASs were simulated in mixed mode as ideal devices using the drift-diffusion model. The simulations show that a diamond DAS promises to outperform an Si DAS when sharpening the kV nanosecond input pulse. The breakdown field and streamer velocity (∼10 times larger in diamond than Si) are likely to be the major reasons enabling kV sub-50 ps switching using a diamond DAS.